Defensive medicine among obstetricians and gynecologists in tertiary hospitals. - Elad Asher; Shay Dvir; Daniel S Seidman; Sari Greenberg-Dotan; Alon Kedem; Boaz Sheizaf; Haim Reuveni (PLoS ONE, 2013)
OBJECTIVE: To describe the daily work practice under the threat of defensive medicine among obstetricians and gynecologists. STUDY DESIGN: A prospective cross-sectional survey of obstetricians and gynecologists working at tertiary medical centers in Israel. RESULTS: Among the 117 obstetricians and gynecologists who participated in the survey, representing 10% of the obstetricians and gynecologists registered by the Israel Medical Association, 113 (97%) felt that their daily work practice is influenced by concern about being sued for medical negligence and not only by genuine medical considerations. As a result, 102 (87%) physicians are more likely to offer the cesarean section option, even in the absence of a clear medical indication, 70 (60%) follow court rulings concerning medical practices, and 85 (73%) physicians mentioned that discussions about medical negligence court rulings are included in their departments' meetings. CONCLUSIONS: Defensive medicine is a well-embedded phenomenon affecting the medical decision process of obstetricians and gynecologists.